Car monitoring using bluetooth security system - Fairuz Rizal, Mohamad Rashidi; Mohd Hisyam, Mohd Ariff; M. Z., Ibrahim (IEEE, 2011)
Security system nowadays become a need for vehicles and available with many modern features. This car security system comes with extra secure access and intelligent alarming. The system only can be accessed and configured by owner using Bluetooth module communication via mobile phone to turn it on or off. In this project, when the alarm is triggered, an intruder alert message will be sent to the user's phone through Bluetooth communication. After the certain time, the alarm system will be triggered and by that time the user have already surrounded the compound and the probability of the intruder to be caught is higher. PIR sensor of the system will continuously monitor movement or present of human in the car. The Bluetooth module will sent intruder alert message as PIC microcontroller receive signal from PIR sensor. The PIC is programmed to wait approximately seven minute before activated the siren. The alarm system status is indicated using LED's indicator to avoid owner accidentally turned it off.